Meningkatkan Daya Tarik Ekowisata Pulau Biawak melalui Penerapan Speedboat Listrik - Pranowo Sidi; Imam Sutrisno; Iskandar; Surya Dharma (Bulletin of Community Engagement, 2024)
Biawak Island, with its rich marine biodiversity, has great potential as an ecotourism destination. However, increasing tourism activities have the potential to threaten environmental sustainability. This research aims to analyze the potential for using electric speedboats as an environmentally friendly transportation solution that can support the development of sustainable ecotourism on Biawak Island. Through literature review, design analysis, and numerical simulation, this research evaluates the performance of electric speedboats in terms of energy efficiency, operational range, and passenger comfort. The research results show that electric speedboats have significant potential to replace conventional fossil fuel-powered speedboats. Apart from being environmentally friendly, electric speedboats also offer other benefits such as lower operating costs in the long term and lower noise levels. The implementation of electric speedboats on Biawak Island is expected to increase tourist attraction, reduce environmental impacts, and support efforts to preserve marine ecosystems.